Implementation of Group Guidance Using Snakes and Ladder Media Self Confidence to Improve Self Confidence - Hasibuan, Nadyah Chusnul Chotimah (INDONESIAN COUNSELING AND PSYCHOLOGY, 2025)
Self-confidence is the belief in one's own ability to do or perform an action, thereby making one feel capable of achieving all of one's goals in life. Low self-confidence will have an impact on the learning and development process of students, so efforts are needed to increase student self-confidence through group counseling services using the self-confidence snake and ladder media. The objectives of this study are to determine 1) the level of students' self-confidence, 2) the implementation of the self-confidence snake and ladder game, and 3) whether the self-confidence snake and ladder game can improve students' self-confidence. This study is a Classroom Action Research in Guidance and Counseling (PTBK). The population of this study is ninth-grade students, and the sample consists of 10 students. The implementation of the confidence snake and ladder game in group counseling was carried out through two cycles. Based on the results obtained, it can be concluded that the pre-cycle condition of the PTBK confidence level of ninth-grade students at SMP Negeri 5 Percut Sei Tuan, as measured by the pre-test, had an average confidence score of 77.3. Furthermore, in Cycle I and Cycle II, group counseling services were provided using the “Snake and Ladder of Self-Confidence” media, resulting in an increase in the self-confidence of ninth-grade students at SMP Negeri 5 Percut Sei Tuan. This increase in self-confidence was evidenced by the post-test results in Cycle II, with an average score of 91.58.